1971
DOI: 10.1002/pol.1971.150090804
|View full text |Cite
|
Sign up to set email alerts
|

Telechelic diene prepolymers. II. Carboxyl‐terminated polydienes

Abstract: Butadiene, isoprene, and chloroprene have been polymerized in dioxane under free‐radical initiation to give liquid prepolymers containing terminal carboxyl groups. 4,4′‐Azobis(4‐cyanovaleric acid) was employed as the initiator. The prepolymers were obtained with molecular weights of 12,000 to 2000 and with functionalities usually greater than 2.0. Experimental parameters were studied to determine their effect on prepolymer yields and properties. The general preparative procedure and prepolymer characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In 1971, Reed reported the synthesis of carboxy-telechelic poly(butadiene) and poly(isoprene) using 4,4′-azobis(4-cyanovaleric acid) as radical initiator; however, this method had poor control over the functionality and materials with a range of functionalities ( F = 1–3.4) were obtained. In 2000, Morita et al reported the synthesis of carboxy-telechelic poly(butadiene) ( F ∼ 2) from ROMP of cis , cis -1,5-cyclooctadiene using cis -1,4-bis(2- tert -butoxycarbonyl)-2-butene as a CTA, followed by acidic deprotection which yielded the carboxy-telechelic polymer .…”
Section: Introductionmentioning
confidence: 99%
“…In 1971, Reed reported the synthesis of carboxy-telechelic poly(butadiene) and poly(isoprene) using 4,4′-azobis(4-cyanovaleric acid) as radical initiator; however, this method had poor control over the functionality and materials with a range of functionalities ( F = 1–3.4) were obtained. In 2000, Morita et al reported the synthesis of carboxy-telechelic poly(butadiene) ( F ∼ 2) from ROMP of cis , cis -1,5-cyclooctadiene using cis -1,4-bis(2- tert -butoxycarbonyl)-2-butene as a CTA, followed by acidic deprotection which yielded the carboxy-telechelic polymer .…”
Section: Introductionmentioning
confidence: 99%
“…very important. Although N,N-dimethylformamide (DMF), acetonitrile and Dox have been proposed [53]; however, Dox was used as the solvent in the present work.…”
Section: Resultsmentioning
confidence: 99%
“…1-4. In the conventional FRP of Bu (reaction B1), conversion reached 54.8% after 2900 min while conversion was only 21.4% after 3300 min in the iodidemediated radical homopolymerization of Bu (reaction B2) where monomer concentration was higher than but initiator concentration was lower (approximately halved) than those in the reaction B1 (Table 1 Due to a limited solubility and low efficiency of ACVA in the pure Bu liquid, solvent should present in the reaction medium to perform a successful reaction [53,54]. For Bu polymerization initiated with ACVA in the bulk state, reaction did not show any conversion after 3930 min in the presence of molecular I 2 (Fig.…”
Section: Conversion Versus Time Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past several years there has been an increasing interest in the synthesis of polymers with low glass transition temperatures and reactive functional groups at each end of a given polymeric chain. They have found use as agents capable of modifying the thermal and mechanical properties of condensation polymers, in the formation of polymeric networks, and as components in the synthesis of block copolymers. Telechelic hydroxyl, amino, and carboxyl , poly(butadiene)s 1 (PBD)s are excellent examples of such polymers that have been employed in the above applications. While these telechelic polymers can be synthesized through the radical or anionic polymerization of 1,3-butadiene using the appropriate initiating or terminating agents, there are several drawbacks.…”
mentioning
confidence: 99%